Prediction of the Risk Factors of Knee Injury During Drop-Jump Landing With Core-related Measurements in Amature Basketball Players - Guo, Liang; Zhang, Jing; Wu, Ying; Li, Li (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: To evaluate the relationship between specific aspects of core stability and knee injury risk factors during drop-jump (DJ) landing. Methods: Eighteen college-aged male amateur basketball players participated in the project. Kinetic and kinematic data for DJ tasks were collected with force plates and infrared cameras. Raw data were processed to calculate knee joint angles and joint moments during DJ landing. Different components of core stability were represented by the sit-ups in 20 seconds (SU), trunk extensor endurance, trunk flexion and extension range of motion, dominant extremity single-leg stance time (DLS), and dominant extremity single-leg hop distance, respectively. Methods: Correlation and regression were used to determine the relationship between jumping-related biomechanical parameters and core stability components. Results: SU shared significant variance with the peak moment of knee extension (PMKE, P<0.05), the peak moment of knee abduction (PMKA, P<0.05), and the angle of knee internal rotation at initial contact (AKRI, P<0.05). DLS shared significant variance with the angular motion of knee internal rotation (AMKR, P<0.05) and the AKRI (P<0.01). SU and DLS together could explain 52% of the variance observed in the AKRI, and the result was significant. Conclusions: Core stability's strength and motor control aspects played an essential role in preventing knee injury during DJ landing. An integrative training program addressing core strength and motor control could be considered for coaches and athletes to prevent knee injury through core training and conditioning.